Two cases with generalised bullous cutaneous reactions after COVID‐19 mRNA vaccine Moderna (Spikevax®) and Pfizer-BioNTech (Comirnaty®) - Charlotte E. Rinnooy Kan; Heike Röckmann; Marijke R. vanDijk; Tanuja Ramsaransing; Lieke L. Reubsaet; Elke E. M. Peters; Lydia E. Vos (Wiley, 2024)
Abstract Bullous cutaneous reactions can be caused by many factors, including vaccines.1 However, among all cutaneous reactions following coronavirus disease 2019 (COVID‐19) mRNA vaccines, bullous reactions are rare. Here, we describe two patients with delayed generalised bullous cutaneous reactions 7 days after receiving  Moderna (Spikevax®) and Pfizer-BioNTech (Comirnaty®) COVID‐19 vaccination, respectively.